Silurian flysch successions of Ellesmere Island, Arctic Canada, and their significance to northern Caledonian palaeogeography and tectonics - Luke P. Beranek; Victoria Pease; Thomas Hadlari; Keith Dewing (2016)
Detrital zircon provenance studies of Silurian flysch units that underlie the Hazen and Clements Markham fold belts of Ellesmere Island, Arctic Canada, were conducted to evaluate models for northern Caledonian palaeogeography and tectonics. Llandovery flysch was deposited along an active plate margin and yields detrital zircons that require northern derivation from the adjacent Pearya terrane. If Pearya originated near Svalbard and NE Greenland, it was transported by strike-slip faults to Ellesmere Island by the Early Silurian. Wenlock to Ludlow turbidites yield Palaeozoic–Archaean detrital zircons with dominant age-groupings c . 650, 970, 1150, 1450 and 1650 Ma. These turbidite systems did not fill a flexural foreland basin in front of the East Greenland Caledonides, but rather an east–west-trending trough that was probably related to sinistral strike-slip faulting along the northern Laurentian margin. The data support provenance connections with the Svalbard Caledonides, especially Baltican-affinity rocks of SW Spitsbergen that were proximal to NE Greenland during the Baltica–Laurentia collision. Pridoli flysch has sources that include Pearya, the East Greenland Caledonides and the Canadian Shield. Devonian–Carboniferous molasse in Arctic Canada has analogous detrital zircon signatures, which implies recycling of Silurian flysch during mid-Palaeozoic (Ellesmerian) collisional tectonism or that some collisional blocks were of similar Baltican–Laurentian crustal affinities.